Leisure-Time Physical Activity and All-Cause Mortality: A Systematic Review - Milan Zelenović; Titta Kontro; Razvan Constantin Dumitru; Nikola Aksovic; Bojan Bjelica; Dan Iulian Alexe; Dragoi Cristian Corneliu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Many scientific studies have been shown the positive effect of physical activity (PA) on reducing morbidity and mortality, whereas physical inactivity is globally one of the leading factors in mortality. Therefore, the purpose was to investigate the relationship between leisure-time physical activity (LTPA) and all-cause mortality among adult population. The data search was performed of 3 electronic databases for the years 2000-2021 February as follows: Google Scholar, PubMed, and ResearchGate. This search was made by using the following terms and operators AND/OR, individually/combination: "physical activity", "physical fitness", "leisure-time physical activity", "all-cause mortality", "risk of death", "mortality". 1220 studies were initially identified, 22 studies were met the inclusion criteria (5 male studies, 2 female studies, 15 both sexes). The results of this systematic review, with total 2568097 participants (aged 20-98 years), showed that any level of PA had health benefits compared to inactivity and sedentary lifestyle. The highest levels of PA had the lowest risk of all-cause mortality. In conclusion, there is an inverse relationship between LTPA and the risk of all-cause mortality, and the harmful effects of physical inactivity may be largely eliminated among those who are most active. So, promoting regular LTPA is strongly associated with well-being, quality of life and reduced the risk of all-cause mortality both in general adult population and elderly population with chronic diseases.